2004
DOI: 10.1089/cap.2004.14.443
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine for the Treatment of Pediatric Nocturnal Enuresis

Abstract: Current treatments for pediatric nocturnal enuresis rely upon the use of behavioral interventions, such as enuresis alarms, and pharmacological interventions, such as antidiuretic hormone analogs, tricyclic antidepressants, and anticholinergics. However, a considerable number of patients do not respond fully to any of these interventions, in spite of optimal behavioral management and medication dosing. This report describes 4 children with attention deficit hyperactivity disorder (ADHD) comorbid with nocturnal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Serotonin and/or noradrenaline reuptake inhibitors (SNRIs) such as atomoxetine are used in the treatment of ADHD as well as anxiety/depression and autism, and there have been some anti-enuretic effects noted in studies [ 28 ]. In children with nocturnal enuresis and ADHD, the use of atomoxetine in combination with other medications was effective in a 4-child case series [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Serotonin and/or noradrenaline reuptake inhibitors (SNRIs) such as atomoxetine are used in the treatment of ADHD as well as anxiety/depression and autism, and there have been some anti-enuretic effects noted in studies [ 28 ]. In children with nocturnal enuresis and ADHD, the use of atomoxetine in combination with other medications was effective in a 4-child case series [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…3 There are reports that the use of atomoxetine in the presence of depression, anxiety, tic disorder, or nocturnal enuresis coexisting with ADHD has possible advantages. [8][9][10] The use of atomoxetine is known to cause side effects such as headache, sleep disorders, increases in blood pressure, cardiac problems, suicidal tendencies, and restlessness. 8,11 However, in the literature, only 1 case report has indicated that atomoxetine causes OCD.…”
Section: Discussionmentioning
confidence: 99%